Effectiveness of comprehensive reproductive health education on adolescent sexual risk behavior and health literacy: quasi-experimental study - Zumrotul Ula; Awatiful Azza; Sitti Zakiyyah Putri; Risna Ayu Rahmadani; Indryani Indryani (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Adolescent sexual risk behavior remains a significant concern in resource-limited settings, often driven by inadequate reproductive health literacy and limited access to accurate information. Comprehensive reproductive health education (CRHE) has been proposed as an integrated approach to address both behavioral and cognitive determinants. This study aimed to evaluate the effectiveness of CRHE in reducing sexual risk behavior and improving health literacy among adolescents. Research Methodology: A quasi-experimental study with a non-equivalent control group design was conducted among 156 adolescents aged 15–19 years. Participants were equally allocated into intervention and control groups. The intervention consisted of structured CRHE sessions delivered over eight weeks. Data were collected using validated questionnaires and analyzed using descriptive statistics, bivariate tests, and multivariate regression models. Statistical significance was set at α = 0.05. Results: The intervention group demonstrated a significantly higher likelihood of reducing sexual risk behavior compared to the control group (OR = 3.12; 95% CI: 1.52–6.38; p = 0.001). Health literacy scores were also significantly improved (β = 11.4; 95% CI: 8.2–14.6; p < 0.001). These findings remained robust after adjusting for potential confounders. Conclusion: CRHE is effective in improving both behavioral and cognitive outcomes among adolescents in resource-limited settings. Integrating such interventions into school-based programs may enhance adolescent health literacy and reduce risky sexual practices. The findings support the implementation of comprehensive, context-sensitive educational strategies as part of broader public health initiatives.